FSM based green memory design and its implementation on ultrascale plus FPGA - Pandey B.; Mohamed R.R.; Tomar G.S.; Hussain D.M.A.; Baker El-Biary Y.A. (Innovare Academics Sciences Pvt. Ltd, 2023)
In this work, we are going to design a memory using Verilog programming in Vivado 2018.3 Integrated Development Environment and implement it on Kintex UltraScale+ FPGA. In order to make it green, we are reducing power dissipation of our design using power supply settings of UltraScale FPGA that support a dual-voltage operation of the primary core fabric. Operating Voltage (VCCINT) of 7 Series (28nm) VNOM, UltraScale (20nm) VNOM, UltraScale+ (16nm) VNOM, and UltraScale+ (16nm) VLOW are 1V, 0.95V, 0.85V, and 0.72V respectively. In our work, we are 0.873 V operating voltage and compare its power dissipation with power dissipation by 0.9V and 0.928 V operating voltage. There is 2.87-6.42 % reduction in power dissipation when we scale down supply voltage from 0.928 V to 0.873 V. 2020 Innovare Academics Sciences Pvt. Ltd. All rights reserved.